Inhibition of microRNA-155 Reduces Neuropathic Pain During Chemotherapeutic Bortezomib via Engagement of Neuroinflammation - Duan, Zongsheng; Zhang, Jian; Li, Jing; Pang, Xiaochuan; Wang, Hushan (Frontiers in Oncology, 2020)
As a chemotherapeutic agent, bortezomib (BTZ) is used for the treatment of multiple myeloma with adverse effect of painful peripheral neuropathy. Our current study was to determine the inhibitory effects of blocking microRNA-155 (miR-155) signal on BTZ-induced neuropathic pain and the underlying mechanisms. We employed real time RT-PCR and western blot analysis to examine the miR-155 and expression of pro-inflammatory tumor necrosis factor-α receptor (TNFR1) in the dorsal horn of the spinal cord. Its downstream signals p38-MAPK and JNK and transient receptor potential ankyrin 1 (TRPA1) were also determined. Mechanical pain and cold sensitivity were assessed by behavioral test. In result, inhibition of miR-155 significantly attenuated mechanical allodynia and thermal hyperalgesia in BTZ rats, which was accompanied with decreasing expression of TNFR1, p38-MAPK, JNK and TRPA1. In contrast, miRNA-155 mimics amplified TNFR1-TRPA1 pathway and augmented mechanical pain and cold sensitivity. In addition, mechanical and thermal hypersensitivity induced by miRNA-155 mimics were attenuated after blocking TNFR1, p38-MAPK, JNK and TRPA1. Overall, we show the key role of miR-155 in modifying BTZ-induced neuropathic pain through TNFR1-TRPA1 pathway, suggesting that miR-155 is a potential target in preventing neuropathic pain development during intervention of BTZ.